LISTENING COMPREHENSION OF ENGLISH AS A SECOND/FOREIGN LANGUAGE; SOCIAL AND COGNITIVE ASPECTS OF DEVELOPMENT AT SECONDARY AND HIGHER SECONDARY LEVELS - Ahmed Bilal Khalid; Afshan Abbasi; Iqra Batool; Tooba Jehan; Iram Sharif (International Journal of Contemporary Issues in Social Sciences, 2024)
The English teaching methods implemented in Pakistan have not successfully achieved the intended goal of communicative competency. Therefore, the circumstances and conditions surrounding the teaching of English as a language or subject in various institutions throughout Pakistan are of great importance to education specialists in the region. English is a mandatory subject at all levels of education in Pakistan, and significant emphasis is placed on it in academic programs. It is expected that Pakistani learners would naturally develop comprehensive language abilities, including listening, enabling them to effectively communicate in English and pursue professions requiring proficiency in the language. To assist language teachers in teaching listening skills at the appropriate level for their classes, this paper conducts a thorough literature review of the cognitive and social aspects of listening, which is crucial given the significance of the English language in Pakistan and the importance of listening comprehension in English language learning.